MORPHOLOGY OF THE LARVAE AND FIRST CRAB OF AN EDIBLE ESTUARINE CRAB. THALAMITA DANAE STIMPSON, 1858 (PORTUNIDAE) FROM INDIAN WATERS - Krishnan, T; Kannupandi, T (Indian Journal of Fisheries, 2011)
Larvae of an edible crab, Thalamita danae Stimpson were reared in tlie laboratory to tiie first crabinstar under conditions of salinity 2S Â± 1 %, temperature 26 =b i*C and photophase 1^12 hr light/dark.First zoea readied first crab instar after six moults, taking at least 26 days. A comparison of the larvaeof Indian and Australian forms is given.